Modeling semiconducting silicene nanostrips: electronics and THz plasmons - Tene, Talia; Guevara, Marco; Borja, Myrian; Mendoza Salazar, María José; Palacios Robalino, María de Lourdes; Vacacela Gomez, Cristian; Bellucci, Stefano (Frontiers in Physics, 2023)
Silicene nanostrips (SiNSs) have garnered significant attention due to their remarkable physical properties, making them an ideal candidate for numerous electronics and plasmonics applications. Their compatibility with current semiconductor technology further enhances their potential. This study aims to investigate the electronic and plasmonic properties of SiNSs with a minimum width of 100 nm using a semi-analytical model that utilizes the carrier velocity of silicene. The carrier velocity was calculated using density functional computations and refined through the GW approximation. Our results reveal that SiNSs with widths ranging from 100 to 500 nm exhibit small bandgaps within the range of a few meV, specifically ranging from 30 to 6 meV, respectively. Furthermore, all the nanostrips analyzed in this study exhibit a √q-like plasmon dispersion within the THz regime (≤35 THz). By varying the experimental setup or the geometric factors of the nanostrips, the associated plasmon THz frequency can be manipulated, resulting in an increase or decrease in frequency or a shift to larger momentum values. Our study serves as a fundamental starting point and a source of inspiration for future experiments, providing a foundation for confirming the results presented in this study.